Technologies for Halide Removal in Water Treatment – A State-of-the-Art Review - Nariyan, Elham; Yu, Qiming Jimmy; Hamilton, David; Li, Qin (The Global Environmental Engineers, 2022)
Halides (X=Cl, Br, I) are naturally present in water, and halide concentrations can be high in water sources that are impacted by high salinity. Halides are also present in wastewater streams from various industrial operations such as pulp and paper, oil and gas, and mining. Drinking water guideline limits have been established for halides, and halide removal from water is important in several ways. Chloride concentration in water is more related to salinity, and its removal from water matters because of adverse health effects, water scarcity, corrosion, and industrial needs. In drinking water treatment, disinfection is essential to improve water quality and prevent the spread of water born pathogens. However, disinfectants also produce harmful disinfection by-products (DBPs) from precursors such as halides and natural organic matter (NOM) in the source water. Removing halides in the source water before disinfection is a preferred option to increase the disinfection efficiency and avoid forming more toxic DBPs. Some industrial-made isotopes are radioactive and carcinogenic, and iodide produces iodinated DBPs. Bromide removal is important because it produces brominated DBPs. Halides also affect AOPs and can cause more active radicals such as OH. and SO4-. to transform into less active radicals. This paper aims to comprehensively review the sources of halides, the chemistry, and interaction in forming DBPs, current regulatory limits and state-of-art removal technologies available, and their challenges.